"Patrimonial Bureaucracy" and Chinese Law: Max Weber's Legacy and Its Limits. (January 2015) - Lai, Junnan
Max Weber's claim that traditional Chinese law was "khadi justice" continues to be a challenge facing scholars of Chinese legal history. While many scholars respond to this thesis at the level of empirical studies, their research cannot replace responses at the theoretical level. Thus, it is necessary to enter into a theoretical dialogue with Weber on the basis of empirical findings. Weber's thought about China within the framework of his sociology of domination is a crucial factor influencing his presentation of Chinese law. In his original theoretical design, "patrimonial bureaucracy" is a mixed or in-between state of irrational and rational types of domination, since it contains elements of both patrimonialism and bureaucracy. Thus, justice and administration under such domination are not completely arbitrary. Weber's assumption that world history increasingly moves toward full rationality, however, induces him to place China in the initial stage of the process of rationalization and to put the modern Western world at the end of that process. Under the influence of this thinking, Weber consciously or unconsciously neglects bureaucratic facets of imperial China's patrimonial bureaucracy and deliberately amplifies its patrimonial facets. As a result, Chinese law in Weber's writings is substantively irrational "khadi justice." Although Weber's concepts and insights are limited, if refined and revised they can still benefit future scholars of traditional Chinese law.